2019
DOI: 10.4257/oeco.2019.2304.04
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Elements as Basis for Conservation of Wetlands and Public Policies in Brazil: The Case of Veredas of the Prata River

Abstract: Vereda is the wetland type of the Cerrado, often associated with the buriti palm Mauritia flexuosa. However, in Mato Grosso do Sul veredas may occur without M. flexuosa, generating legal misinterpretation and environmental damages, such as drainage for agriculture. As a case study, we inventoried the flora of natural and drained veredas of the Prata River, pointing out key-species for identification of veredas without M. flexuosa, providing subsidies for their characterization. We recorded 157 species (44 fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the Yucatan peninsula of Mexico, Thompson-Ambriz et al (2020) recorded sawgrass in inland brackish marsh habitats, and Lara-Domínguez et al (2005) and Munguía-Rosas and Montiel (2014) found sawgrass intermixed with dwarf mangroves. In the wetlands of the Prata River in Brazil, Pott et al (2019) indicated that sawgrass is a dominant species in habitats with other species of sedges and bunch grasses.…”
Section: Habitatsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Yucatan peninsula of Mexico, Thompson-Ambriz et al (2020) recorded sawgrass in inland brackish marsh habitats, and Lara-Domínguez et al (2005) and Munguía-Rosas and Montiel (2014) found sawgrass intermixed with dwarf mangroves. In the wetlands of the Prata River in Brazil, Pott et al (2019) indicated that sawgrass is a dominant species in habitats with other species of sedges and bunch grasses.…”
Section: Habitatsmentioning
confidence: 99%
“…Cladium jamaicense occurs along the Atlantic coast of Mexico, Central America, and Brazil (Escalera-Vázquez et al ., 2019; Hernandez et al ., 2015; Lara-Domínguez et al ., 2005; Munguía-Rosas and Montiel, 2014; Pott et al ., 2019; Rejmánková et al ., 1995; Thompson-Ambriz et al ., 2020). Sawgrass is widely distributed in the Caribbean (Azan and Webber, 2006; Correll and Correll, 1972; Imbert and Delbé, 2006).…”
Section: Geographical Distributionmentioning
confidence: 99%
See 1 more Smart Citation